Varietal Evaluation of Pomegranate under Arid Conditions - Prasad, R N (Annals of Arid Zone, 2016)
ArilOng the nine cultivars of pomegranate evaluated, cv. Jodhpur Red, P-23 and Basin Seedless were more vigorous than other cultivars. Jalore Seedless showed its superiority with respect to fruit size, juice content, softness of seeds and other characters. The cracking percentage of fruits was maximum (63.4%) in . cv. Jodhpur Red and minimum in cv. Jalore Seedless (21.2%).